Pengabdian kepada Masyarakat melalui Kegiatan Donor Darah di RS Bhayangkara Watukosek - Putu Ayu Dhana Reswari; Yustisia Amalia; Cityta Putri Kwarta; Lentera Afrida Kusumawardani; Wiwid Samsulhadi; Sasi Widuri (Rena Cipta Mandiri, 2025)
The issue of blood availability remains a challenge in healthcare services, particularly in meeting transfusion needs in hospitals. Low participation in voluntary blood donation and limited public understanding, including among university students, regarding the importance of donation contribute to the imbalance between blood demand and supply. This community service activity aims to increase voluntary blood donation participation through the involvement of Universitas Dr. Soetomo students as agents of social awareness at RS Bhayangkara Watu Kosek. The activity was conducted offline through brief education, donor health screening, and blood donation implementation in collaboration with hospital healthcare professionals. The participants consisted of 50 Universitas Dr. Soetomo students, comprising 15 males and 35 females. Results indicated that all eligible participants successfully donated blood, and there was a marked improvement in students' understanding and positive attitudes toward blood donation as a form of social and humanitarian concern. This activity demonstrates that student-based community service is effective in supporting hospital blood availability while simultaneously building students' social character. The outcomes of this service serve as an important model for sustainable collaboration between universities and hospitals in supporting healthcare services.